The immunomodulating effect of palmitoylethanolamide on human myeloid dendritic cells and its possible impact on Alzheimer’s disease - Piccolino, Iliana; Iannuzzi, Filomena; Lionetti, Ludovica; Mazzonello, Benedetta; Barreca, Valeria; Banaj, Nerisa; Arezzini, Valentina; Piras, Fabrizio; Bossù, Paola (Frontiers in Immunology, 2026)
Palmitoylethanolamide (PEA) is an endogenous fatty acid amide that has emerged as a promising therapeutic candidate for neurodegenerative disorders, particularly Alzheimer’s disease (AD). Recognized for its inherent anti-inflammatory, analgesic, immunomodulatory, and neuroprotective properties, PEA possesses a good potential as a novel treatment addressing neuroinflammation associated with neurodegeneration, even though its precise mechanisms of action remain to be fully understood. Dendritic cells (DCs) are specialized migratory innate immune cells that play a crucial role in initiating and regulating immune responses and inflammation in both the body and the brain. In AD, DCs display a dysfunctional, pro-inflammatory profile, suggesting their involvement in disease pathology and progression. To explore the therapeutic potential of PEA, this study investigated its effects in vitro on human monocyte-derived DCs under both normal and AD-like conditions. The results show that PEA exerts significant immunomodulatory effects, promoting the maturation of DCs in both healthy and disease states. Notably, PEA treatment appears to correct the dysregulated state of DCs observed in AD conditions. This study reveals a novel mechanism by which PEA modulates immune activity through its action on DCs. By restoring normal DC function in neurodegenerative settings, PEA may help reduce inflammation, highlighting its potential as a therapeutic agent for Alzheimer’s disease.